Challenges in Differentiated Learning: Perspective of Pre-Service English Teachers under the Merdeka Curriculum - Sarvita, Oky Agus; Soraya, Irma; Nafiah, Marfuatin (ICONELT, 2024)
Pre-service teachers need to have a complete comprehension of the Merdeka Curriculum because they will use their pedagogical knowledge to utilize it effectively. The participants in this study are (pre-service teacher) from English Education Department students who have enrolled in teaching internship program. This study explores pre-service teachers' understanding and experiences with the Merdeka Curriculum through qualitative methods, using structured interviews to gather insights on its application during teaching practices. Findings reveal that while pre-service teachers gain practical knowledge through direct classroom experiences, they face challenges in lesson planning, time management, and differentiated instruction due to limited resources and experience. Teachers struggle with managing diverse student abilities and maintaining engaging learning environments, often relying on adaptive strategies and continuous professional development to overcome these obstacles. The study highlights the importance of tailored teaching approaches, effective lesson planning, and ongoing teacher support to ensure successful curriculum implementation. The Merdeka Curriculum aims to foster critical thinking and adaptability in students, while also enhancing teachers' ability to meet diverse learner needs in a flexible educational framework.